PENINGKATAN KEAKTIFAN BELAJAR PESERTA DIDIK MELALUI METODE TIME TOKEN MATA PELAJARAN IPS PADA SISWA KELAS IV SD INPRES 53 KABUPATEN SORONG - Natalya Tutuarima; Haryo Franky Souisa (LPPM Politeknik Saint Paul Sorong, 2023)
In learning students tend to be passive. It is very difficult for students to be more active, creative and confident. For example, students do not dare to ask if they do not understand the material explained by the teacher. Low student learning outcomes (70% of students have not met the KKM). This study aims to prove the increase in the activity of students towards learning outcomes through the time token method in Social Studies class IV subjects. The research was conducted at SD Inpres 53, Sorong Regency in May 2023. This research was a quasi-experimental design in the form of a non-equivalent control group design. Data was collected through observation, questionnaires and documentation. Then analyzed using descriptive data analysis techniques. Based on the findings in the research that has been done, the researchers concluded that there was an increase in the activity of students through the time token method for social studies subjects in class IV SD SD Inpres 53, Sorong Regency. Students whose classes are implemented by the time token method are more active in learning than students whose classes are not implemented by the time token method. In addition, student learning outcomes in classes that applied the time token method increased compared to those that did not apply the time token method. Keywords : time token method, student activity, social studies learning outcomes